Android app : image processing using opencv4android library - Chua, Wei Xuan (2018)
In this upcoming world of technology, smartphones are most commonly used because of its portability, functions and the ability to make phone calls. Statistics have shown that there is an increase of 1.49 billion of social media users in the world from 2010 to 2017, and it is predicted that there would be even more users in the upcoming years [1]. People tend to capture memories using their smartphones’ camera, edit and process them, and post the images and videos up on their social media accounts, such as Facebook and Instagram, to share with their family and friends. E-books, websites and document readings are also done using smartphone apps in the recent years. Documents can be easily emailed to other users by scanning and processing their documents into their smartphone and attaching it in the email. For smartphone users to use real time processing and filtering, computer vision techniques can be used. This project aims to develop an Android app supported by Open Source Computer Vision Library, also known as OpenCV library. The app would include filters, face detection, automatic selfie to allow users to have an optimised interactive use of the in-built camera in the app as well as the function to edit their images and videos efficiently. A document scanning function is also available in the app to allow users to scan and process their documents. The edited and scanned images can then be saved in the smartphone’s storage and shared to social media apps. The application, named SnapSociety, was developed in Java language and C++ on Android Studio with OpenCV4 Android Library, which will be easy to use and have a user-friendly interface for optimal usage.